THE APPLICATION OF THE MUDHARABAH SYSTEM IN COMMUNITY FOREST MANAGEMENT IN BIREUEN REGENCY, NANGGROE ACEH DARUSSALAM - Halim Amran Mutasodirin; Rizal Eko Kurniawan (Media Syari'ah, 2017)
The manufacture of the community forest should be improved, considering are still many empty land that is unproductive and needs of wood is very large. The community forest is the forest growing above the ground that burdened a right belongs to the community with the provisions of broad minimum 0.25 ha, closure of tree canopiesand other plants more than 50 %.Bireuën Regency in Aceh Province will plan development the community forest of 191 hectares with aid programs of the provincial government.The community have not been able to manage the forest maximally. Therefore, still have to need empowerment in the community forest management. Mudharabah system is an economic system of Islam or often called system for results with for sharing profit and loss without interest rates. The Percentage division results using mutual agreement. When using mudharabah system, the community will become more prosperous and aggressive in developing thecommunity forest. One of all purpose of this idea is the realization communityforest management of Mudharabah system. Lacking empowerment and insufficient capital to be the reason for the community not interested to manage the community forest. Mudharabah system provides convenience in managing the community forest involving investors, cooperatives, local community as a farmer, and the Village Government.